Assessment of Levels of Interferon Gamma (IFN-γ) and Interleukin-15 as Markers in Patients with Celiac Disease - Eidan, Jalal Sabr; Mubark, Hawraa Ameer (Medical Science Journal for Advance Research, 2024)
Background: Celiac disease (CD) is a long-term digestive disorder caused by the immune system that affects people who are inherently more likely to get it. The ingestion of gluten-containing meals or beverages triggers the condition in those who are sensitive. The study aimed to serum levels of Tissue Transglutaminase (tTG-IgA and tTG-IgG), Interferon gamma (IFN-γ) and Iterleukin-15 in patients with celiac disease. Materials and methods: This case-control investigation was conducted at Marjan Hospital, Imam AL-Sadiq Hospital, and Al-Imam Ali Hospital. A convenience sampling of 146 samples. The study consisted of 73 patients with celiac disease (CD) and 73 healthy controls. 5 mL of venous blood was donated by each participant and subsequently deposited in gel containers (6 ml). The tubed blood is centrifuged at 3000 rpm for 10 minutes. The serum for Tissue Transglutaminase (tTG-IgA and tTG-IgG), Interferon gamma (IFN-γ) and Iterleukin-15 are stored in Eppendorf containers at -20 ºC until it is thawed on the day of the ELISA. Results: The present study found that patients had significantly higher levels of IL-15 (23.374±7.016) compared to controls (16.632±3.680), p-value < 0.001. In addition, the results report that Interferon gamma level was 11.268±5.381 in patients with celiac disease are higher significantly than the controls 7.461±2.304 with P. value <0.001. Conclusions: There was significant elevating in levels of Interferon gamma (IFN-γ) and Iterleukin-15 in patients with celiac disease. Furthermore, the study found that tTG IgA and IgG show a significant positive correlation. In addition, there was positive correlation between Interferon gamma with tTG (IgA and IgG), and IL-15.